2021
DOI: 10.5194/gmd-2020-412
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fast and accurate learned multiresolution dynamical downscaling for precipitation

Abstract: Abstract. This study develops a neural network-based approach for emulating high-resolution modeled precipitation data with comparable statistical properties but at greatly reduced computational cost. The key idea is to use combination of low- and high- resolution simulations to train a neural network to map from the former to the latter. Specifically, we define two types of CNNs, one that stacks variables directly and one that encodes each variable before stacking, and we train each CNN type both with a conve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Due to the stochastic and high-dimensionality nature of many physical processes of the Earth system, GANs and conditional GANs are particularly appealing for atmospheric science problems. Recently, they have been used for various Earth-science related applications: for instance for statistical downscaling Wang et al 2021), temporal disaggregation of spatial rainfall fields (Scher and Peßenteiner 2020), sampling of extreme values (Bhatia et al 2020), modelling of chaotic dynamical systems (e.g., Xie et al 2018;Wu et al 2020), classification of snowflake images , weather forecasting (Bihlo 2020) and stochastic parameterization in geophysical models (Gagne II et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the stochastic and high-dimensionality nature of many physical processes of the Earth system, GANs and conditional GANs are particularly appealing for atmospheric science problems. Recently, they have been used for various Earth-science related applications: for instance for statistical downscaling Wang et al 2021), temporal disaggregation of spatial rainfall fields (Scher and Peßenteiner 2020), sampling of extreme values (Bhatia et al 2020), modelling of chaotic dynamical systems (e.g., Xie et al 2018;Wu et al 2020), classification of snowflake images , weather forecasting (Bihlo 2020) and stochastic parameterization in geophysical models (Gagne II et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have already demonstrated their potential in earth science related applications. Super resolution CNNs have been applied to radar data (Geiss and Hardin, 2020a), wind and solar modeling (Stengel et al, 2020), satellite remote sensing (Liebel and Körner, 2016;Lanaras et al, 2018;Müller et al, 2020), precipitation modeling (Wang et al, 2021), and climate modeling (Vandal et al, 2018;Baño Medina et al, 2020).…”
Section: Cnns For Downscaling Atmospheric Datamentioning
confidence: 99%
“…AI has several methods that are well suited to this challenge. Artificial neural networks have proven successful at embedding multiple sources of data [30,31] and mapping complex non-linear input-outputs relationships. In particular, techniques such as generative adversarial networks have been successful at enhancing the resolution of outputs and will be used to obtain the most detailed representation of the quantities of interest [32].…”
Section: Narrativementioning
confidence: 99%